Improving Stability and Absorption of Minerals in Pharmaceutical Formulations: A Review of Emerging Strategies - Pitriani; Yoga Windhu Wardhana; Chaerunisaa, Anis Yohana (Chempublish Journal, 2025)
Minerals are essential for numerous physiological functions. However, their application in pharmaceutical formulations is often limited by hygroscopicity and low bioavailability, which can diminish their therapeutic effectiveness. This article reviewa not only highlights these challenges but also provides an in-depth, up-to-date evaluation of various strategies designed to overcome these limitations, supported by quantitative data from recent literature. This review article emphasizes the role of co-processing with excipients and encapsulation technology, which improve mineral stability by creating an effective moisture barrier, thereby extending product shelf life. Effervescent formulations, through an acid-base reaction, generate gas that significantly enhances mineral solubility and contributes to increased bioavailability. Microencapsulation, using a polymer or protein layer, protects minerals from gastric degradation and allows for controlled release in the intestine, the primary site of absorption. Chelating peptides form stable complexes with mineral ions, improving their transport and uptake in the body. Meanwhile, advanced nanoparticle technologies like Solid Lipid Nanoparticles and liposomes increase the contact surface area, accelerate dissolution, and protect minerals from oxidative degradation. This review article offers a comprehensive overview of strategies that can significantly advance the development of more effective and stable mineral-based pharmaceuticals.